2016
DOI: 10.1111/jfpe.12421
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Microwave‐Assisted Extraction of Bioactive Compounds from Coriolus versicolor Mushroom Using Response Surface Methodology

Abstract: Response surface methodology was applied to optimize microwave-assisted extraction (MAE) of total phenolic content (TPC) and antioxidant activity from fruiting bodies of Coriolus versicolor mushroom, and to compare its efficiency with conventional reflux extraction. A central composite design was employed for the optimization of three MAE parameters including extraction time (X 1 , min), ethanol concentration (X 2 , %) and microwave power (X 3 , W) for the highest yield of TPC and antioxidant activity measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 30 publications
5
26
0
3
Order By: Relevance
“…3 ). This is in accordance with Maeng et al [ 24 ] who mentioned that the extraction time during MAE significantly affected the TPC values and antioxidant capacity of Coriolus versicolor mushroom extracts. Similar results were reported by Zhang et al [ 14 ] who noted that during MAE the yields of phenolic compounds of A. blazei significantly increased from 1 to 5 min and then slightly decreased.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…3 ). This is in accordance with Maeng et al [ 24 ] who mentioned that the extraction time during MAE significantly affected the TPC values and antioxidant capacity of Coriolus versicolor mushroom extracts. Similar results were reported by Zhang et al [ 14 ] who noted that during MAE the yields of phenolic compounds of A. blazei significantly increased from 1 to 5 min and then slightly decreased.…”
Section: Resultssupporting
confidence: 92%
“…These results are in accordance with Zhang et al [ 14 ] who found that during MAE, high microwave power (500 W) enhanced the yields of phenolic compounds of A. blazei , while at higher microwave power (700 W) the yields declined. Similarly, Maeng et al [ 24 ] also reported that the microwave power significantly affected the TPC values and antioxidant capacity of Coriolus versicolor mushroom extracts. The microwave power is a parameter that should be included in an RSM design in future studies aiming to optimize the recovery of TPC and antioxidants from shiitake mushrooms.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Among RSM designs, central composite design (CCD) is the most widely used approach for statistical process optimization. Along with process and product optimization, RSM provides the additional advantages of low cost and enhanced quality, accompanied by reduced total number of required experimental runs (Ameer et al, 2017b;Maeng et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, extraction process is affected by various factors such as, temperature, time, solid to solvent ratio, choice of solvent, and nature of raw material (Tiwari, 2015). Therefore, for developing an efficacious extraction process, a crucial step is the optimization of the experimental conditions and RSM (a mathematical model) (Maeng, Shahbaz, Ameer, Jo, & Kwon, 2017) is employed for the optimization of variables in the recent extraction studies.…”
Section: Introductionmentioning
confidence: 99%